Ornamental Plants of Home Garden along the Coridor of Kopendukuh Village, Banyuwangi, East Java-Indonesia as a Basis for Ecotourism Planning - Sihombing, Maic A.L.; Rohie, Ade M.C.; Februyani, Nawafila; Swandayani, Rosalina E. (Graduate School, Universitas Brawijaya, 2015)
Home garden is a habitat for many plants species which are important in planning and management of tourism in rural area. Ornamental plants have crucial function to increase the appearance of homes and buildings through landscaping. The purpose of this study is to analyze ornamental plants species which grow in the home garden along the corridor of Kopendukuh Village as one of the potential attractions of tourism development. The observation of ornamental plants diversity was carried out at home gardens along the rural coridor of Kopendukuh Village. Totally, there are about 10 home gardens were assessed. In each home gardens, plans species were recorded and identified systematically. Qualitative analysis was performed using analysis of sociability, vitality, and periodicity. Result of the survey confirm that home garden is home of about 40 ornamental plants species. These species came from 24 family. About 59% of the ornamental species was classified as individual plant species live in small groups, 28% of ornamental plant was classified as shrubs. About 65% of are ornamental plant without flowers and seeds.Â The diversity of plants in home garden needs special attention, especially in order to increase settlement visual quality. Keywords: Kopendukuh, ornamental plant, sociability, vitality, periodicity.